Energy efficiency of LTE macro base station - Abdulkafi A.A.; Kiong T.S.; Koh J.; Chieng D.; Ting A.; Ghaleb A.M. (2023)
The growing energy consumption in wireless networks driven by dramatic increases in mobile users and network traffic, are putting mobile operators under immense challenges towards meeting the demands of both cost reduction and environment conservation. The network Energy Efficiency (EE) considers not only energy consumed by the base station (BS), but also the capacity and coverage of the network. In this paper we study the impact of modulation and coding schemes (MCS), bandwidth (BW) size and transmitted power on the energy efficiency of a LTE macro base station. Although it is very much expected that higher transmission power results in lower EE, the difference actually diminishes when cell size increases. At around 1200m it is found that the EE are almost equal for all transmission power considered. On the other hand, EE increases significantly as the BW increases. Similar effect on EE is observed when MCS changes from lower order to higher order scheme. In fact EE becomes more sensitive to MCS change at higher bandwidth. 2012 IEEE.